ANALISIS PENGGUNAAN MEDIA WORDWALL UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN BAHASA INDONESIA DI SDN PARSANGA IV - Agung Wibowo Nursuhandi Miftahol; Agung Wibowo Nursuhandi (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to analyze the use of wordwall media to increase students' interest in learning Indonesian language lessons at SDN Parsanga IV. The research method used is descriptive qualitative method which aims to provide an in-depth description of experiences and perceptions related to the phenomenon to be studied. Qualitative data acquisition was carried out by observation, interview, and documentation. This research was conducted at SDN Parsanga IV. The results showed that the use of wordwall media in Indonesian language lessons was able to attract students' interest in learning which could be seen from the increase in student activeness and involvement during the learning process. Indonesian language learning on the material of majas and stylistics which was originally difficult to understand by students because students were less focused during the learning process has now turned into fun and interesting because the wordwall display is able to attract students' attention with a variety of templates.